2021
DOI: 10.1542/peds.2020-1330
|View full text |Cite|
|
Sign up to set email alerts
|

Sensor-Based Electronic Monitoring for Asthma: A Randomized Controlled Trial

Abstract: BACKGROUND: Although sensor-based monitoring of daily inhaled corticosteroids (ICSs) and short-acting β-agonist medications may improve asthma outcomes, the effectiveness of these interventions in diverse pediatric populations remains unclear. METHODS: Caregiver and child dyads were randomly assigned to receive inhaler sensors that allowed for caregiver and clinician electronic monitoring of medications. End points included A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…We recruited parents from the intervention arm of the Improving Technology-Assisted Recording of Asthma Control in Children (iTRACC) trial for interviews [ 15 ]. In the original trial, caregiver and child dyads were eligible if the following criteria were met: (1) child was aged 4 to 17 years; (2) child had experienced at least one asthma exacerbation requiring oral corticosteroids in the year prior to enrollment; and (3) parent reported active prescription of an ICS or combination ICS–long-acting beta-agonist (ICS-LABA) for at least 1 year prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recruited parents from the intervention arm of the Improving Technology-Assisted Recording of Asthma Control in Children (iTRACC) trial for interviews [ 15 ]. In the original trial, caregiver and child dyads were eligible if the following criteria were met: (1) child was aged 4 to 17 years; (2) child had experienced at least one asthma exacerbation requiring oral corticosteroids in the year prior to enrollment; and (3) parent reported active prescription of an ICS or combination ICS–long-acting beta-agonist (ICS-LABA) for at least 1 year prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…The iTRACC trial involved a multicomponent health intervention that included (1) Bluetooth-enabled sensors placed on inhaler medications that paired with the parent’s smartphone via a mobile app (Propeller Health), and (2) monitoring through a web portal and follow-up phone calls by clinic staff [ 15 , 18 ] ( Figure 1 ). The EMM technology tracked the use of most ICSs, short-acting beta-agonists (SABAs), and combination ICS-LABAs that were available on the US market.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 An electronic monitoring sensor attached to inhalers has proven to increase asthma control in paediatric patients, as well as caregivers quality of life. 61 A multi‐centre observational study concluded that a gamification strategy using a mobile app could be useful to monitor adherence to asthma medication. 62 Additionally, patients’ feedback on these devices has also been described to be positive.…”
Section: Ehealth For Patients and Patient Representativesmentioning
confidence: 99%
“…A recent observational study described a 14.5% increase in inhalers adherence by using digital trackers among patients with asthma and COPD during the COVID‐19 pandemic 60 . An electronic monitoring sensor attached to inhalers has proven to increase asthma control in paediatric patients, as well as caregivers quality of life 61 . A multi‐centre observational study concluded that a gamification strategy using a mobile app could be useful to monitor adherence to asthma medication 62 .…”
Section: Ehealth For Patients and Patient Representativesmentioning
confidence: 99%